1998
DOI: 10.1021/la980042p
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical Properties of Elastic Polymeric Materials As Probed by Scanning Force Microscopy

Abstract: Scanning force microscopy (SFM) was used for probing micromechanical properties of compliant polymeric materials. Classic models of elastic contacts, Sneddon's, Hertzian, and JKR, were tested for various indentation depths and for a variety of polymeric materials. We selected extremely compliant polyisoprene rubbers (Young's modulus, E ) 1-3 MPa), elastic polyurethanes (E ) 5-50 MPa), and hard surfaces of polystyrene (PS) and polyvinylchloride (PVC) (E ) 1-5 GPa). Both Sneddon's and Hertzian elastic models gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
195
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(205 citation statements)
references
References 17 publications
(37 reference statements)
10
195
0
Order By: Relevance
“…A comparison of the reliability of Hertz and JKR theories on polymers can be found in Refs. [276,277]. Also the effect on the sample deformation of maximum load [278], contact time [279], and loading rate [280] have been characterized.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the reliability of Hertz and JKR theories on polymers can be found in Refs. [276,277]. Also the effect on the sample deformation of maximum load [278], contact time [279], and loading rate [280] have been characterized.…”
Section: Resultsmentioning
confidence: 99%
“…28,29 As the sample is probed by the tip at a constant force, soft regions will deform more than stiff regions. Thus, soft regions will appear to be lower in height.…”
Section: Resultsmentioning
confidence: 99%
“…We collected the data in a 32 x 32 array and extracted adhesive force values (pull-off forces as defined by the force-distance curve 169 ) and elastic compression moduli. 170 (a) (b) (c) Collected for 32 x 32 pixels, lateral size is 3 x 3 jim.…”
Section: Micromechanical and Surface Properties Of Ps Brush Layermentioning
confidence: 99%
“…Elastic moduli and adhesive forces are much lower along the debris area, but they are very homogeneous on the PS layer surface far from the damaged area. From the analysis of elastic modulus depth profiles according to Chizhik et al, 170 we concluded that the AFM tip indents and compresses very thin polymer layers and probes the underlying solid substrate. However, after tip retraction, the initial surface morphology (thickness, roughness, homogeneity) is completely restored without any trace of high local compression.…”
Section: Micromechanical and Surface Properties Of Ps Brush Layermentioning
confidence: 99%
See 1 more Smart Citation